Analisis Pemasaran Kambing Saburai di Desa Gisting Atas Kecamatan Gisting Kabupaten Tanggamus - tina, Suhartina; Herdiansah, Riko (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2024)
Livestock farming is one of the agricultural sectors that has an important role in supporting people's need for consumption of animal protein. Animal husbandry is not only directed at increasing production but is expanded into processing and marketing (Agribusiness). Goats are one of the small ruminant livestock that has great potential to be developed in Indonesia, especially in Gisting District because it has enormous potential to be developed in Indonesia, apart from providing animal protein needs, but also as a way to improve the community's economy. Goats are small ruminants that are relatively easy to maintain and can eat a variety of forages, especially young leaves. Goats also adapt very quickly to the place where they are kept so that goats can also live in rocky areas, forests and mountains. BPS 2018, the goat population in Indonesia reached 18,720,706 heads, 53.76% of which were found on the island of Java and the rest were spread outside Java, including in Lampung Province. Lampung Province is the province with the highest goat population compared to other regions outside Java. The population reached 1,297,872 individuals. The population of Saburai goats alone in 2018 reached 3000 heads. Marketing is a process and managerial process that enables individuals or groups to get what they need by creating, offering and exchanging products of value to other parties or all activities related to the delivery of products or services from producers to consumers. Research Objectives: To determine the characteristics of marketing institutions involved in marketing Saburai goats, to understand marketing functions, to understand marketing efficiency analysis and price determination at Saburai goat farmers in Gisting District. The method used in this research is a survey method with respondents who are marketing goats. saburai are breeders and buyers. Surveys are a method of collecting primary data by asking individual respondents questions in the form of a questionnaire. Keywords: marketing, saburai goat